The Gruffalo - Donaldson, Julia; Scheffler, Axel (New York : Puffin Books, 2006)
A mouse invents stories of the Gruffalo in order to scare other animals away from eating him. When a real Gruffalo shows up, what will he do?
Originally published: Great Britain : Macmillan Children's Books, 1999.
Keywords: Animals -- Fiction; Curiosity -- Fiction; Mice -- Fiction; Stories in rhyme